Age Friendly Universities and engagement with older adults: moving from principles to practice. Issue 5 (2nd September 2016) - Talmage, Craig A.; Mark, Rob; Slowey, Maria; Knopf, Richard C.
Abstract: The global society is facing a new burgeoning element: an ageing population. Response to the educational needs and interests of older adults requires innovative pedagogies and practices of teaching, research, and community engagement. While traditionally geared towards provision for younger adults, the case is presented that universities have the potential to play a major role in innovation for later life learning for older adults. This article outlines one approach, the Age Friendly University (AFU) and highlights 10 principles that offer a possible guide for innovation and institutional change. The integration of AFU's mission and principles into three universities is reflected in stories from three university cases in Ireland, the UK (Scotland) and the USA exploring potential merits and also major challenges. It is argued the AFU has the potential to bring social, personal and economic benefits to older adults and universities alike.